Recent advances in aptasensors based on graphene and graphene-like nanomaterials - Ping, Jianfeng (2017)
Graphene and graphene-like two-dimensional nanomaterials have aroused tremendous research interest in recent years due to their unique electronic, optical, and mechanical properties associated with their planar structure. Aptamers have exhibited many advantages as molecular recognition elements for sensing devices compared to traditional antibodies. The marriage of two-dimensional nanomaterials and aptamers has emerged many ingenious aptasensing strategies for applications in the fields of clinical diagnosis and food safety. This review highlights current advances in the development and application of two-dimensional nanomaterials-based aptasensors with the focus on two main signal-transducing mechanisms, i.e. electrochemical and optical. A special attention is paid to graphene, a one-atom thick layer of graphite with exceptional properties, representing a fastgrowing field of research. In view of the unique properties of two-dimensional nanostructures and their inherent advantages of synthetic aptamers, we expect that high-performance two-dimensional nanomaterials-based aptasensing devices will find extensive applications in environmental monitoring, biomedical diagnostics, and food safety.